Functional Tn5393-Like Transposon in the R Plasmid pRAS2 from the Fish Pathogen Aeromonas salmonicida subspecies salmonicida Isolated in Norway - L'Abée-Lund, Trine M. (American Society for Microbiology, 2000)
Tn5393c containing strA-strB was identified as part of R plasmid pRAS2 from the fish pathogen Aeromonas salmonicida subsp. salmonicida. This is the first time an intact and active transposon in the Tn5393 family has been reported in an ecological niche other than an agricultural habitat.